Options for improving agricultural water productivity under increasing water scarcity in South Africa - Mabhaudhi, Tafadzwanashe; Mpandeli, S.; Nhamo, Luxon; Senzanje, Aidan; Chimonyo, Vimbayi Grace Petrova; Modi, Albert Thembinkosi (2019)
South Africa is ranked among the thirty driest countries in the world, a challenge that is negatively affecting agricultural production. Other challenges such as population growth, rural-urban migration, changing food preferences and drought exacerbate pressure on agricultural water productivity. The review critically assessed the different considerations for increasing agricultural water productivity under water scarce conditions in South Africa. While under these conditions, irrigation may seem an obvious solution to increasing agricultural water productivity as a response to frequent droughts and mid-season dry spells. However, considerations on the availability of water and energy for irrigation expansion and the accessibility of irrigation services to different farming groups in the country. It is generally argued that irrigation is an expensive option and not necessarily readily accessible to most farmers. There are prospects for tapping into South Africa’s groundwater resources but the extent to which they can contribute to expanding area under irrigation is contested given the challenges of quantifying and pumping the water. Most smallholder farmers currently lack access to water, energy, infrastructure and technical skills to irrigate thus making irrigation a challenging option in this sector. An alternative would be to explore rainwater harvesting and soil water conservation technologies, which involve inducing, collecting, storing and conserving runoff water for agriculture. The drawbacks to this are that, apart from scale issues, rainfall is becoming more erratic and droughts more frequent and hence the feasibility of this approach under frequent drought could be challenged.